Analisis nilai pendidikan karakter dalam novel Hati Suhita karya Khilma Anis: Kajian psikologi sastra - Nur’aini, Aisyah (Maliki Interdisciplinary Journal, 2024)
The novel "Hati Suhita" describes the twists and turns of a household built on the basis of an arranged marriage. This novel attracts publics attention because there is no antagonist in it, all characters experience their own destiny, with this novel, "Hati Suhita" implies character education values. This research aims to analyze the character education values contained in the novel. The research method used is a qualitative approach with content analysis. The results of this analysis shows several character education values contained in the novel. Based on the results of the study, it can be concluded that there are character education values related to oneself; 1) religious values, 2) honest values, 3) disciplinary values, 4) hard work, 5) creative values, 6) independent values and 7) curiosity values. As for the others it includes; 1) friendly/communicative values, 2) social care, and 3) responsibility. Overall, the novel "Hati Suhita" by Khilma Anis contains many important character education values. This research provides insight into the importance of character education in shaping good personalities and building harmonious relationships with others.